2020
DOI: 10.1364/ol.394873
|View full text |Cite
|
Sign up to set email alerts
|

Video-rate lensless endoscope with self-calibration using wavefront shaping

Abstract: Lensless fiber endoscopes are of great importance for keyhole imaging. Coherent fiber bundles (CFB) can be used in endoscopes as remote phased arrays to capture images. One challenge is to image at high speed while correcting aberrations induced by the CFB. We propose the combination of digital optical phase conjugation, using a spatial light modulator, with fast scanning, for which a 2D galvo scanner and an adaptive lens are employed. We achieve the transmission of laser and image scanning through the CFB. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The standard deviation of the measured FWHM is only 0.55%, which denotes a robust wavefront shaping in our system. A similar approach was employed for focus scanning [22] and simple wavefront shaping [19] through the MCF. For complex wavefront shaping using SLMs, both the intensity and phase information at the target plane are required to reconstruct the desired light field.…”
Section: Phase Distortion Compensation In a Multi-core Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of the measured FWHM is only 0.55%, which denotes a robust wavefront shaping in our system. A similar approach was employed for focus scanning [22] and simple wavefront shaping [19] through the MCF. For complex wavefront shaping using SLMs, both the intensity and phase information at the target plane are required to reconstruct the desired light field.…”
Section: Phase Distortion Compensation In a Multi-core Fibermentioning
confidence: 99%
“…Nevertheless, DOPC is required to compensate for the optical path difference between cores which can lead to phase distortion when light propagating through an MCF [16][17][18]. Focus scanning employing simple wavefront shaping through MCFs is thus achieved [19][20][21][22], paving the way to lensless endoscopy. Besides, dynamic wavefront control in an MCF-based dual-beam trap enables optical manipulation of the cell-orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive optics technology has been employed in various systems to improve imaging properties, 1 correct aberrations, 2 and perform self-calibration. 3 Imaging techniques that acquire information in a point-wise manner, such as confocal microscopy 4,5 or optical coherence microscopy, 6,7 require point-scanning in three dimensions to obtain three-dimensional (3D) data. One possible way to accomplish the axial scanning is to mechanically translate the sample 8,9 or the microscope objective 10 in z-direction.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the TM-based approaches, Czarske et al [29,30,31] have demonstrated in-situ measurement of the fiber phase-distortions by adding a partially-reflecting mirror to the MCF distal-facet, and correction using a spatial light modulator (SLM). However, as imaging is performed by raster scanning a phase-corrected focus, correction of dynamic distortions is challenging, and fluorescence labeling is required.…”
Section: Main Text Introductionmentioning
confidence: 99%